Integrated Analysis of Hi-C and RNA-Seq Reveals the Molecular Mechanism of Autopolyploid Growth Advantages in Pak Choi (Brassica rapa ssp. chinensis) - Wu, Huiyuan; Song, Xiaoming; Lyu, Shanwu; Ren, Yiming; Liu, Tongkun; Hou, Xilin; Li, Ying; Zhang, Changwei (Frontiers in Plant Science, 2022)
Polyploids generated by the replication of a single genome (autopolyploid) or synthesis of two or more distinct genomes (allopolyploid) usually show significant advantages over their diploid progenitors in biological characteristics, including growth and development, nutrient accumulation, and plant resistance. Whereas, the impacts of genomic replication on transcription regulation and chromatin structure in pak choi have not been explored fully. In this study, we observed the transcriptional and genomic structural alterations between diploid B. rapa (AA) and artificial autotetraploid B. rapa (AAAA) using RNA-seq and Hi-C. RNA-seq revealed 1786 differentially expressed genes (DEGs) between the diploids and autotetraploids, including 717 down-regulated and 1069 up-regulated genes in autotetraploids. Of all the 1786 DEGs, 23 DEGs (10 down-regulated DEGs in autotetraploids) were involved in Compartment A-B shifts, while 28 DEGs (20 up-regulated DEGs in autotetraploids) participated in Compartment B-A shifts. Moreover, there were 15 DEGs in activated TADs (9 up-regulated DEGs in diploids) and 80 DEGs in repressed TADs (49 down-regulated DEGs in diploids). Subsequently, eight DEGs with genomic structural variants were selected as potential candidate genes, including four DEGs involved in photosynthesis (BraA01003143, BraA09002798, BraA04002224, and BraA08000594), three DEGs related to chloroplast (BraA05002974, BraA05001662, and BraA04001148), and one DEG associated with disease resistance (BraA09004451), which all showed high expression in autotetraploids. Overall, our results demonstrated that integrative RNA-seq and Hi-C analysis can identify related genes to phenotypic traits and also provided new insights into the molecular mechanism of the growth advantage of polyploids.